Polymorphisms of Lewis and Secretor genes are related to breast cancer and metastasis in axillary lymph nodes - Teresa, Debora Barreto [UNESP]; Santos, Raquel Alves; Takahashi, Catarina Satie; Carrara, Helio H.; Moreira, Haroldo Wilson [UNESP]; Mattos, Luis Carlos; Lia-Neto, Nicolino; Cunha, Leonardo A.; Bassi, Carmem Lucia; Soares, Edson Garcia; Donadi, Eduardo Antonio; Mello, Elaine Rodrigues [UNESP]; et al. (Springer, 2010)
ABH and Lewis antigen expression has been associated with cancer development and prognosis, tumor differentiation, and metastasis. Considering that invasive ductal breast carcinoma (IDC) presents multiple molecular alterations, the aim of the present study was to determine whether the polymorphism of ABO, Lewis, and Secretor genes, as well as ABO phenotyping, could be associated with tumor differentiation and lymph nodes metastasis. Seventy-six women with IDC and 78 healthy female blood donors were submitted to ABO phenotyping/genotyping and Lewis and Secretor genotyping. Phenotyping was performed by hemagglutination and genotyping by the polymerase chain reaction with sequence-specific primers. ABO, Lewis, and Secretor genes were classified by individual single nucleotide polymorphism at sites 59, 1067, 202, and 314 of the Lewis gene, 428 of the Secretor gene, and 261 (O1 allele), 526 (O2 and B allele), and 703 (B allele). No association was found between breast cancer and ABO antigen expression (P = 0.9323) or genotype (P = 0.9356). Lewis-negative genotype was associated with IDC (P = 0.0126) but not with anatomoclinical parameters. Nonsecretor genotype was associated with axillary lymph node metastasis (P = 0.0149). In conclusion, Lewis and Secretor genotyping could be useful to predict respectively breast cancer susceptibility and axillary lymph nodes metastasis.
Keywords: ABO; Lewis; Secretor; Genotyping; Phenotyping; Human breast cancer